Analyzing the Foot and Mouth Disease outbreak as from 2008 to 2014 in cattle and buffaloes in Sri Lanka - Umanga C. Gunasekera (2018)
© 2017 Elsevier B.V. Foot and Mouth Disease (FMD) is a highly contagious disease that affects all cloven hoofed animals and causes considerable economic losses to cattle and buffalo farmers worldwide. FMD is endemic to Sri Lanka. The objective of this study was to analyze the past situation of FMD from 2008 to 2014 in the country and to identify relevant risk factors associated with the 2014 outbreak. Outbreak data from the Department of Animal Production and Health, Sri Lanka from 2008 to 2014 were used to describe the spatial distribution and to determine associations between the frequency of outbreaks across the country (nine provinces) and factors including vaccination coverage and outbreak year. A questionnaire was used to collect the information on potential risk factors for FMD for the 2014 outbreak from case farms (n = 83) and control farms (n = 161). Seven focus group (FG) discussions with farmers and five in-depth interviews with veterinarians and livestock officers were conducted. A negative binomial regression model was constructed to determine the relationship between frequencies of outbreaks by province, year, vaccine coverage and bovine numbers per province. A logistic regression model was used to determine the association between potential risk factors and disease status of the farm. There was no association between vaccination coverage and outbreak frequencies at province level (Risk Ratio = 1.02; 95% CI = 0.09, 1.05). Based on our cases-control study there were five variables significantly associated with the FMD spread: cattle/buffalo contact with nearby villages (Odds Ratio = 2.88; 95% CI: 1.23–6.72), cattle/buffalo grazing near water tank areas (OR = 3.11;95% CI: 1.21–7.97), animals bought or sold during the outbreak (OR = 3.3; 95% CI: 1.39–7.83), being near to a road where animal traders travel (OR = 3.44 95% CI: 1.10–10.79), and being fed on the floor instead of feed troughs (OR = 2.61,1.08–6.31). The major risk factor identified here was cattle/buffalo movement by means of grazing/trading. Both focus group discussions and the questionnaire ascertained that the vaccination had no effect in the most recent outbreak. Results from this study are expected to support veterinary services in developing effective control measures during future outbreaks.